Contemplation as a Corrective to Technological Education - Steel, Sean (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
<!–[if gte mso 9]> Normal 0 <![endif]–>This paper argues that “noetic studies,” contemplation, or theoria ought to take greater precedence in education than is currently the case. Our modern focus on and fascination with information technologies serves in many ways to thwart and to discourage the cultivation of noetic studies and the pursuit of wisdom in schools. The suggestion throughout this paper is that if the significance of pre-modern and non-technological ways of knowing could be made clear and convincing to educational policy-makers, it seems likely that the appropriateness of such pursuits might be recognized, and their practice rendered more frequent as a kind of “corrective” to technological education.